Surviving in a new host: Eight years of monitoring translocated aroids, bromeliads, and orchids in the Andean forests in Colombia - Benavides, Ana María; Calderón-Caro, Jennifer; Canal, Dubán (Frontiers in Forests and Global Change, 2023)
Vascular epiphytes are extraordinary diverse in the Tropical Andean region reaching up to 50% of vascular plant species diversity at local scale. Compared to trees and terrestrial herbs, epiphytes are more vulnerable to forest alteration due to their structural dependence of trees and environmental requirements. Based on experimental approaches for ecological purposes, monitoring air pollutants, and seeking propagation alternatives, rescue and translocation of vascular epiphytes (mainly bromeliads and orchids) from a threatened forest to a safer forest have been recently conducted in Colombia. Preliminary assessments indicate that epiphytes benefit from such well-planned measures and their mortality and survival might be associated with extrinsic and intrinsic factors which remain to be understood. We evaluated the role of both intrinsic (foliar area, number of leaves, initial pseudobulbs, stems or rosettes, functional group and epiphyte species) and extrinsic (host tree species, bark water holding capacity, type of substrate, location on host tree, nutrients, and hormone addition) factors on survival of 16 vascular epiphyte species after translocation into a secondary forest in Antioquia (Colombia) during 8 years. Also, we assess the effect of precipitation bioclimatic variables on plant survival. Overall mortality rate in this study ranked among 1-7 % year1, survival decreases annually reaching 44 % by the end of the eighth year. Host tree species and intrinsic factors such as functional group and epiphyte species had a significant effect on the probability of survival. Bromeliads in particular exhibited high mortality, which could be explained by their monocarpic growth form. Another group of species showing high mortality were the miniature orchids, Masdevalia amanda, M. platyglossa, associated with short life cycles. Five host tree species showed an effect on survival; however, it is not clear which factors or characteristics affect it. A higher seasonality of precipitation was related to the percentage of overall mortality. This indicates that although epiphytes are adapted to minimum levels of annual precipitation, they are more affected by extreme precipitation events or drought which reduces its longevity. Based on our results, Andean forests can recover ecological attributes obtained by the epiphyte assemblages by introducing and effectively maintaining populations of epiphyte species.